An Exploratory Study on the Impact of Senior Management at Chinese Companies After Pandemic in Hong Kong, China - Kei, Chan Yee (Digital Repository of Theses, 2023)
The definition of impact of the pandemic in this research is mainly categorized in a few focused areas: 1) Purchasing behavior, 2) mindset change, 3) Attitude or perspectives on the future in Hong Kong 4) workstyle or mode of work. The purpose of the research is to understand or to clarify how the pandemic has changed the way people lead their workstyle and living style as well as mindset. Through this research study, I obtained a verification among the senior management or higher-ranking employees on how they perceive the future of the economy, purchasing behavior, lifestyle and workstyle through in-depth interviews and survey questionnaires, which the findings is well illustrated in the Result section. The scope of the participants varies across a wide spectrum of industries at senior management levels, specifying the generation they are under as well as their job industry. The results provide quite a significant representation and overview picture on the mentality on how the pandemic affected their attitude towards living and the world perspectives. The Pandemic has placed a significant lifestyle and attitude change on people’s lives but at the same time it also brings possibilities and new directions business opportunities as well. Pandemic somewhat reshaped Hong Kong people perceive what is truly important in our heart, throughout these three significant years, fighting together as a community and team. A period of time of forced self-reflection and a redefinition of how to lead life and live life, and how business and management should operate to optimize both results and efficiency. The pandemic, retrospectively speaking, was a moment of stillness where true learning takes place and to redefine the meaning of life and purposes.